Preparation method of B4C synergistic Ti reinforced aluminum-based composite material

Through the preparation method of B4C synergistic Ti reinforced aluminum-based composite, the problem of difficult to guarantee cracking tendency and weld quality during welding of aluminum-based composite materials is solved, and the effect of improving welding strength and weld quality is achieved. It is suitable for aluminum alloys and aluminum Industrial application of matrix composite materials.

CN119242974APending Publication Date: 2025-01-03BEIJING NORTH VEHICLE GROUP CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411296377.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Aluminum-based composite materials are prone to cracking tendencies and difficult to guarantee the quality of welds during welding.

Method used

The preparation method of B4C synergistic Ti reinforced aluminum-based composite material is adopted. By mixing B4C powder and Ti powder, high-energy pre-ball milling is performed using a planetary mill to obtain reinforced powder, and the ball mill is mixed with Al powder step by step, followed by cold pressing forming. , sintering and solid solution + aging treatment to prepare B4C synergistic Ti reinforced aluminum matrix composite material.

Benefits of technology

It effectively improves the strength and weld quality of aluminum-based composite materials, reduces welding defects, and is suitable for the rapid molding process of aluminum alloys and aluminum-based composite materials, improving manufacturing efficiency and welding quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a B4C and Ti reinforced aluminum-based composite material, which comprises the following steps: firstly, mixing B4C powder and Ti powder, and carrying out high-energy pre-ball-milling by using a planetary ball mill to realize uniform mixing and particle refinement; and step-by-step mixing and ball milling are conducted on the reinforced powder and the Al powder, so that the reinforced phase is evenly distributed in the Al powder, namely the Al-based composite powder is obtained, and meanwhile the bonding tendency of the Al powder in the ball milling process is reduced. And the prepared composite powder is subjected to cold press molding, sintering and solid solution and aging, and the B4C and Ti synergistic reinforced aluminum-based composite material is prepared. The excellent physical and chemical properties of B4C and Ti are utilized, B4C and Ti are introduced into the aluminum-based composite material to improve the mechanical properties of the aluminum-based composite material and the weld quality of corresponding products, and the method has important significance on industrial application of the aluminum-based composite material and lightweight design of the products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy, and specifically relates to a preparation method of a B4C synergistically Ti-reinforced aluminum-based composite material. Background Art

[0002] Aluminum-based composite materials have broad application prospects in various fields (civil, medical, automotive, aerospace, military, etc.) due to their excellent mechanical properties, corrosion resistance and low density. Especially in the manufacturing and research and development of high-strength, lightweight and low-energy consumption products, the application advantages of aluminum-based composite materials are more prominent.

[0003] In engineering applications, due to the structural characteristics of the product, aluminum-based composite materials cannot achieve integrated molding of the product. Welding or fasteners (bolts, nuts, rivets, etc.) are often used to connect various structures (frames, attachments, ribs, etc.). Therefore, the performance indicators of the weld and the coordination between the fasteners and the aluminum-based structural parts are particularly important. However, when the strength and hardness of aluminum-based composite materials are greatly improved, the heat input process of weld formation is prone to evaporation, loss of the strengthening phase, and the generation of pores, making it difficult to ensure the quality of the weld.

[0004] At present, reducing welding defects of aluminum-based composite materials and improving weld quality are important research contents to promote their high-quality engineering applications. According to the characteristics of powder metallurgy rapid prototyping, the micro-control of the strengthening phase and microstructure in the aluminum matrix can be targeted through weld defect analysis to adapt to different welding needs and application scenarios. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The present invention proposes a preparation method of a B4C-Ti reinforced aluminum-based composite material to solve the technical problems of reducing the weld cracking tendency of the aluminum-based composite material and optimizing the weld quality.

[0007] (II) Technical solution

[0008] In order to solve the above technical problems, the present invention proposes a preparation method of a B4C synergistic Ti reinforced aluminum-based composite material, the preparation method comprising: mixing B4C powder and Ti powder, performing high-energy pre-ball milling with a planetary ball mill to obtain a reinforced powder; performing step-by-step mixing and ball milling of the reinforced powder and Al powder to obtain an Al-based composite powder; and sequentially cold pressing, sintering, and solid solution + aging the Al-based composite powder to prepare a B4C synergistic Ti reinforced aluminum-based composite material.

[0009] Furthermore, the preparation method specifically comprises:

[0010] S1. Place B4C powder, Ti powder and Al powder into a vacuum drying oven for vacuum drying;

[0011] S2. The dried B4C powder and Ti powder are placed in a stainless steel ball mill, steel balls are added, and the stainless steel ball mill is placed in a vacuum box and evacuated;

[0012] S3. Pre-high-energy ball milling of a stainless steel ball mill is performed by a planetary ball mill to obtain a reinforced powder;

[0013] S4. Add pure Al powder to the reinforced powder, add steel balls, put the stainless steel ball mill into a vacuum box, evacuate the vacuum box, and perform high-energy ball milling on the stainless steel ball mill using a planetary ball mill to complete a ball milling process;

[0014] S5. Pure Al powder was added to the powder obtained after the first ball milling, steel balls were added, the stainless steel ball mill was placed in a vacuum box and evacuated, and the stainless steel ball mill was subjected to high-energy ball milling by a planetary ball mill to complete the secondary ball milling to obtain an Al-based composite powder;

[0015] S6. The Al-based composite powder is added to a tableting mold by a tablet press, cold pressed, and after the pressing is completed, the sample is removed;

[0016] S7. The pressed sample is sintered in atmosphere, kept warm, and cooled in the furnace to obtain a sintered sample;

[0017] S8. The sintered sample is subjected to solid solution + aging treatment to obtain a B4C synergistic Ti reinforced aluminum-based composite material.

[0018] Furthermore, in step S1, the drying temperature is 60-100° C., and the drying time is 1-5 hours.

[0019] Furthermore, in step S2, B4C powder is 40-60wt%, and the rest is Ti powder; the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, and the mass ratio of small balls, medium balls, and large balls is 2:3:5; the vacuum degree of the vacuum box is -0.1MPa.

[0020] Furthermore, in step S3, the rotation speed of the pre-high energy ball mill is 150-300 r / min, and the ball mill is rotated for 10-30 min and then paused for 5-10 min, and then rotated in the reverse direction, and the total ball milling time is 2-10 h.

[0021] Furthermore, in step S4, pure Al powder is added to the reinforcing powder, and the mass ratio of the reinforcing powder is adjusted to 10-50wt%; the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, and the mass ratios of small balls, medium balls, and large balls are 2:3:5; the vacuum degree of the vacuum box is -0.1MPa; the rotation speed of the high-energy ball mill is 100-200r / min, and it pauses for 5-10min every 10-30min of rotation, and then rotates in the opposite direction, and the total ball milling time is 2-10h.

[0022] Furthermore, in step S5, pure Al powder is added to the powder obtained after the first ball milling, the mass ratio of the powder in the first ball milling is adjusted to 5-20wt%, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, the mass ratio of small balls, medium balls, and large balls is 2:3:5, the vacuum degree of the vacuum box is -0.1MPa, the rotation speed of the high-energy ball mill is 100-150r / min, and it is paused for 5-10min every 10-30min of rotation, and then reverse rotation is performed. The total ball milling time is 2-10h.

[0023] Furthermore, in step S6, vaseline is applied on the gasket side of the tableting mold to prepare for sample preparation, 6 g of Al-based composite powder is added to the tableting mold with a diameter of 30 mm through a tablet press, and cold pressing is performed at a pressure of 500 to 800 MPa for 5 to 20 minutes.

[0024] Furthermore, in step S7, high-purity argon is introduced during sintering, the sintering temperature is 550-610°C, the heating rate is 5-15°C / min, and the temperature is kept for 2-5 hours.

[0025] Furthermore, in step S8, during the solution treatment, the solution temperature is 450-480°C, the holding time is 1-2h, and water cooling is performed to obtain a supersaturated solid solution; during the aging treatment, the aging temperature is 150-200°C, the heating rate is 5°C / min, and the holding time is 6-10h.

[0026] (III) Beneficial effects

[0027] The present invention proposes a preparation method of a B4C-Ti reinforced aluminum-based composite material. First, B4C powder and Ti powder are mixed, and high-energy pre-ball milling is performed using a planetary ball mill to achieve uniform mixing and particle refinement. The reinforced powder and Al powder are mixed and ball-milled step by step to achieve uniform distribution of the reinforcing phase in the Al powder, that is, Al-based composite powder, while reducing the bonding tendency of the Al powder during the ball milling process. The prepared composite powder is subjected to cold pressing, sintering, solid solution + aging to obtain a B4C-Ti reinforced aluminum-based composite material. The present invention utilizes the excellent physical and chemical properties of B4C and Ti, introduces them into aluminum-based composite materials, and is used to improve the mechanical properties of aluminum-based composite materials and the weld quality of corresponding products, which is of great significance to the industrial application of aluminum-based composite materials and lightweight design of products.

[0028] The beneficial effects of the present invention specifically include:

[0029] (1) The synergistic reinforcement of Al-based composites by B4C and Ti can effectively improve the strength of Al-based composites. According to the performance characteristics of the two reinforcement phases, the Al-based composites can be promoted in engineering applications, reduce weld defects and improve welding quality.

[0030] (2) By pre-ball milling the dried reinforced powder, a certain mass ratio can not only reduce the adhesion of the powder caused by ball milling, but also reduce the particle size, which is conducive to uniform distribution in the subsequent composite powder.

[0031] (3) In the preliminary ball milling, B4C and Ti form a powder film on the surface of the stainless steel ball and the wall of the ball mill, which promotes the refinement of Al powder particles, reduces Al powder adhesion, reduces the operation process and strengthens the loss of powder for the subsequent step-by-step high-energy ball milling. The refined composite powder is conducive to the subsequent formation of Al-based composite materials with good density, and at the same time plays a role in improving the strength of the material.

[0032] (4) It can be used for the rapid prototyping process of attachments of aluminum alloys and aluminum-based composite materials, which not only improves the manufacturing efficiency but also makes it easy to form good weld quality during the attachment welding. DETAILED DESCRIPTION

[0033] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with embodiments.

[0034] The present invention provides a method for preparing a B4C-Ti reinforced aluminum-based composite material, which specifically comprises the following steps:

[0035] S1. Place B4C powder, Ti powder and Al powder in a vacuum drying oven for vacuum drying at a drying temperature of 60 to 100°C for a drying time of 1 to 5 hours.

[0036] By drying the desired powder, the moisture adsorbed on the surface of the powder can be removed to avoid defects in the preparation of the composite material.

[0037] S2. Put the dried B4C powder and Ti powder into a stainless steel ball mill, wherein the B4C powder is 40-60wt% and the rest is Ti powder; add steel balls with a ball-to-material ratio of 10:1, and the diameters of the steel balls are 3mm, 5mm, and 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), and put the stainless steel ball mill into a vacuum box to evacuate the vacuum to -0.1MPa.

[0038] By using a higher proportion of B4C powder (40-60wt%), the Ti powder can be diluted and the adhesion of Ti powder during ball milling can be reduced. The ball-to-material ratio of 10:1 can reduce the loss of strengthening powder, and the vacuum ball milling environment can effectively prevent the oxidation of Ti powder.

[0039] S3. Pre-high-energy ball milling of the stainless steel ball mill is performed by a planetary ball mill at a rotation speed of 150-300 r / min. After every 10-30 min rotation, pause for 5-10 min. Check and ensure that the clamping tools of the ball mill are tightened and not loose. Then reverse rotation is performed. The total ball milling time is 2-10 h to obtain a reinforced powder with refined particles and uniform mixing.

[0040] By subjecting B4C powder and Ti powder to high-energy ball milling at a relatively high speed (150-300 r / min), not only can the crushing, grinding and mixing of the reinforced powder by the stainless steel balls be accelerated, effectively reducing the particle size, but also the thin film formed by the powder on the wall of the ball mill and the surface of the stainless steel balls can be strengthened, thereby reducing the wettability of Al with the wall of the ball mill and the surface of the stainless steel balls.

[0041] S4. Add pure Al powder to the reinforcing powder, adjust the mass ratio of the reinforcing powder to 10-50wt%, add steel balls, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate, the vacuum degree is -0.1MPa, and perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 150-200r / min. Pause for 5-10min every 10-30min rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 1-5h to complete one ball milling.

[0042] By directly mixing pure Al powder with refined strengthening powder in a certain proportion, the operation process can be simplified and materials can be saved. A higher speed (150-200r / min) can not only make the strengthening particles and aluminum powder evenly mixed, but also help to refine Al powder particles. At the same time, the low wettability of Al powder with the wall of the ball mill and the surface of the stainless steel ball can reduce the bonding tendency of Al powder.

[0043] S5. Add pure Al powder to the powder obtained after the first ball milling, adjust the mass ratio of the powder in the first ball milling to 5-20wt%, add steel balls, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate it, the vacuum degree is -0.1MPa, and perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 100-150r / min. Pause for 5-10min every 10-30min rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 2-10h, and the secondary ball milling is completed to obtain Al-based composite powder.

[0044] By continuing to add a certain proportion of pure Al powder into the ball mill, the ratio of the strengthening powder and Al powder can be controlled.

[0045] S6. Apply vaseline on the side of the gasket of the tableting mold to prepare for sample preparation. Add 6g of Al-based composite powder into the tableting mold with a diameter of 30mm through a tablet press. Cold press molding is performed at a pressure of 500 to 800MPa. The pressure holding time is 5 to 20min. After the pressing is completed, take out the sample.

[0046] By pressing the Al-based composite powder, the residual air can be removed and the density of the sample can be improved by maintaining the pressure.

[0047] S7. The pressed sample is subjected to atmosphere sintering (introducing 99.999% high-purity argon) at a sintering temperature of 550-610°C and a heating rate of 5-15°C / min. After keeping the temperature for 2-5 hours, the sample is cooled in the furnace to obtain a sintered sample.

[0048] S8. The sintered sample is subjected to solution treatment + aging treatment, wherein, during the solution treatment, the solution temperature is 450-480°C, the holding time is 1-2h, and water cooling is performed to obtain a supersaturated solid solution; during the aging treatment, the aging temperature is 150-200°C, the heating rate is 5°C / min, and the holding time is 6-10h to eliminate stress and homogenize the structure to obtain a B4C synergistic Ti-reinforced aluminum-based composite material.

[0049] The principle of the present invention is as follows: (1) B4C and Ti are selected as strengthening phases. Since B4C has high hardness, low density and good chemical stability, it is easier to achieve uniform distribution in aluminum-based composite materials, and its morphology and distribution are relatively stable in the subsequent welding of composite materials; Ti has good mechanical properties and a high melting point. While strengthening the Al-based composite materials, the subsequent welding heat input is not easy to cause welding defects caused by evaporation and loss, and the formation of needle-shaped brittle phase Al3C4 is inhibited, which is beneficial to improving the quality of the weld. (2) High-energy ball milling is preferentially performed on high-hardness B4C and Ti to refine the particles, which can reduce the adhesion of Ti particles in high-speed ball milling. (3) The use of step-by-step and different speed powder mixing ball milling can reduce the particle size of Al powder, reduce adhesion, and ensure uniform mixing of composite powders. (4) Cold pressing is adopted to use high pressure to remove residual air in the composite powder, and the plastic flow of Al can achieve good density of the sample. (5) Atmosphere sintering is used to eliminate the influence of air in the furnace on the sample, ensuring the sintering quality of the sample. Through subsequent solid solution + aging treatment, the plasticity and toughness of the sample are improved, the structure is homogenized, and the mechanical properties of the Al-based composite material are improved.

[0050] Example 1

[0051] S1. Place B4C powder, Ti powder and Al powder in a vacuum drying oven for vacuum drying at a temperature of 60°C for 2 h.

[0052] S2. Put the dried B4C powder and Ti powder into a stainless steel ball mill, wherein the B4C powder is 40wt% and the rest is Ti powder; add steel balls with a ball-to-material ratio of 10:1, and the diameters of the steel balls are 3mm, 5mm, and 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), and put the stainless steel ball mill into a vacuum box and evacuate the vacuum to -0.1MPa.

[0053] S3. Pre-high-energy ball milling of the stainless steel ball mill is performed by a planetary ball mill at a speed of 200r / min. After every 10min rotation, pause for 10min, check and ensure that the clamping tools of the ball mill are tightened and not loose, and then reverse rotation is performed. The total ball milling time is 2h to obtain a reinforced powder with refined particles and uniform mixing.

[0054] S4. Add pure Al powder to the reinforcing powder, adjust the mass ratio of the reinforcing powder to 20wt%, add steel balls, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate it, the vacuum degree is -0.1MPa, and perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 150r / min. Pause for 10min after every 20min of rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 2h, and one ball milling is completed.

[0055] S5. Add pure Al powder to the powder obtained after the first ball milling, adjust the mass ratio of the powder in the first ball milling to 10wt%, the ball-to-material ratio to 10:1, the diameters of the steel balls to 3mm, 5mm, and 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate it to a vacuum degree of -0.1MPa, perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 100-150r / min, pause for 5-10min every 10-30min rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 2h, and the secondary ball milling is completed to obtain Al-based composite powder.

[0056] S6. Apply vaseline on the gasket side of the tableting mold to prepare for sample preparation. Add 6 g of Al-based composite powder into the tableting mold with a diameter of 30 mm through a tablet press. Cold press molding is performed at a pressure of 550 MPa. The pressure is maintained for 10 minutes. After the pressing is completed, the sample is taken out.

[0057] S7. The pressed sample was subjected to atmosphere sintering (introducing 99.999% high-purity argon) at a sintering temperature of 560°C and a heating rate of 10°C / min. After keeping the temperature for 3 hours, the sample was cooled in the furnace to obtain a sintered sample.

[0058] S8. The sintered samples were subjected to solution treatment + aging treatment, wherein, during the solution treatment, the solution temperature was 450°C, the holding time was 2h, and water cooling was performed to obtain a supersaturated solid solution; during the aging treatment, the aging temperature was 150°C, the heating rate was 5°C / min, and the holding time was 6h to eliminate stress and homogenize the structure to obtain a B4C synergistic Ti-reinforced aluminum-based composite material.

[0059] Example 2

[0060] S1. Place B4C powder, Ti powder and Al powder in a vacuum drying oven for vacuum drying at a temperature of 80°C for 1 h.

[0061] S2. Put the dried B4C powder and Ti powder into a stainless steel ball mill, wherein the B4C powder is 60wt% and the rest is Ti powder; add steel balls with a ball-to-material ratio of 10:1, and the diameters of the steel balls are 3mm, 5mm, and 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), and put the stainless steel ball mill into a vacuum box and evacuate the vacuum to -0.1MPa.

[0062] S3. Pre-high-energy ball milling of the stainless steel ball mill is performed by a planetary ball mill at a speed of 250r / min. After every 10-minute rotation, pause for 10 minutes to check and ensure that the clamping tools of the ball mill are tightened and not loose. Then reverse rotation is performed. The total ball milling time is 2 hours to obtain a reinforced powder with refined particles and uniform mixing.

[0063] S4. Add pure Al powder to the reinforcing powder, adjust the mass ratio of the reinforcing powder to 20wt%, add steel balls, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate it, the vacuum degree is -0.1MPa, and perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 150r / min. Pause for 10min after every 20min of rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 2h, and one ball milling is completed.

[0064] S5. Add pure Al powder to the powder obtained after the first ball milling, adjust the mass ratio of the powder in the first ball milling to 5wt%, the ball-to-material ratio to 10:1, the diameters of the steel balls to 3mm, 5mm, and 7mm (the mass ratio of small balls, medium balls, and large balls is 2:3:5), put the stainless steel ball mill into a vacuum box and evacuate it to a vacuum degree of -0.1MPa, perform high-energy ball milling on the stainless steel ball mill with a planetary ball mill at a speed of 100r / min, pause for 10min after every 20min of rotation, check and ensure that the clamping tool of the ball mill is tightened and not loose, and then rotate in the opposite direction. The total ball milling time is 2h, and the secondary ball milling is completed to obtain Al-based composite powder.

[0065] S6. Apply vaseline on the gasket side of the tableting mold to prepare for sample preparation. Add 6 g of Al-based composite powder into the tableting mold with a diameter of 30 mm through a tablet press. Cold press molding is performed at a pressure of 600 MPa. The pressure is maintained for 10 minutes. After the pressing is completed, the sample is taken out.

[0066] S7. The pressed sample was subjected to atmosphere sintering (introducing 99.999% high-purity argon) at a sintering temperature of 580°C and a heating rate of 10°C / min. After being kept at this temperature for 2 hours, the sample was cooled in the furnace to obtain a sintered sample.

[0067] S8. The sintered samples were subjected to solution treatment + aging treatment, wherein, during the solution treatment, the solution temperature was 480°C, the holding time was 2h, and water cooling was performed to obtain a supersaturated solid solution; during the aging treatment, the aging temperature was 150°C, the heating rate was 5°C / min, and the holding time was 6h to eliminate stress and homogenize the structure to obtain a B4C synergistic Ti-reinforced aluminum-based composite material.

[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a B4C-Ti reinforced aluminum-based composite material, characterized in that: The preparation method comprises the following steps: mixing B4C powder and Ti powder, and performing high-energy pre-ball milling with a planetary ball mill to obtain a reinforced powder; performing step-by-step mixing and ball milling on the reinforced powder and Al powder to obtain an Al-based composite powder; and sequentially performing cold pressing, sintering, and solid solution + aging on the Al-based composite powder to prepare a B4C-Ti reinforced aluminum-based composite material.

2. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 1, characterized in that: The preparation method specifically comprises: S1. Place B4C powder, Ti powder and Al powder into a vacuum drying oven for vacuum drying; S2. The dried B4C powder and Ti powder are placed in a stainless steel ball mill, steel balls are added, and the stainless steel ball mill is placed in a vacuum box and evacuated; S3. Pre-high-energy ball milling of a stainless steel ball mill is performed by a planetary ball mill to obtain a reinforced powder; S4. Add pure Al powder to the reinforced powder, add steel balls, put the stainless steel ball mill into a vacuum box, evacuate the vacuum box, and perform high-energy ball milling on the stainless steel ball mill using a planetary ball mill to complete a ball milling process; S5. Pure Al powder was added to the powder obtained after the first ball milling, steel balls were added, the stainless steel ball mill was placed in a vacuum box and evacuated, and the stainless steel ball mill was subjected to high-energy ball milling by a planetary ball mill to complete the secondary ball milling to obtain an Al-based composite powder; S6. The Al-based composite powder is added to a tableting mold by a tablet press, cold pressed, and after the pressing is completed, the sample is removed; S7. The pressed sample is sintered in atmosphere, kept warm, and cooled in the furnace to obtain a sintered sample; S8. The sintered sample is subjected to solid solution + aging treatment to obtain a B4C synergistic Ti reinforced aluminum-based composite material.

3. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S1, the drying temperature is 60-100° C., and the drying time is 1-5 hours.

4. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S2, B4C powder is 40-60wt%, and the rest is Ti powder; the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, and the mass ratio of small balls, medium balls, and large balls is 2:3:5; the vacuum degree of the vacuum box is -0.1MPa.

5. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S3, the rotation speed of the preliminary high-energy ball mill is 150-300 r / min, and the mill is rotated for 10-30 min and then paused for 5-10 min, and then rotated in the reverse direction, and the total ball milling time is 2-10 h.

6. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S4, pure Al powder is added to the reinforcing powder, and the mass ratio of the reinforcing powder is adjusted to 10-50wt%; the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, and the mass ratios of small balls, medium balls, and large balls are 2:3:5; the vacuum degree of the vacuum box is -0.1MPa; the speed of the high-energy ball mill is 100-200r / min, and it pauses for 5-10min every 10-30min of rotation, and then rotates in the opposite direction, and the total ball milling time is 2-10h.

7. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S5, pure Al powder is added to the powder obtained after the first ball milling, the mass ratio of the powder in the first ball milling is adjusted to 5-20wt%, the ball-to-material ratio is 10:1, the diameters of the steel balls are 3mm, 5mm, and 7mm, the mass ratio of small balls, medium balls, and large balls is 2:3:5, the vacuum degree of the vacuum box is -0.1MPa, the rotation speed of the high-energy ball mill is 100-150r / min, and it is paused for 5-10min every 10-30min of rotation, and then reverse rotation is performed. The total ball milling time is 2-10h.

8. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S6, vaseline is applied on the gasket side of the tableting mold to prepare for sample preparation, 6 g of Al-based composite powder is added to the tableting mold with a diameter of 30 mm through a tablet press, and cold pressing is performed at a pressure of 500 to 800 MPa for 5 to 20 minutes.

9. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S7, high-purity argon is introduced during sintering, the sintering temperature is 550-610°C, the heating rate is 5-15°C / min, and the temperature is kept for 2-5 hours.

10. The method for preparing a B4C-Ti reinforced aluminum-based composite material according to claim 2, characterized in that: In step S8, during the solution treatment, the solution temperature is 450-480°C, the holding time is 1-2h, and water cooling is performed to obtain a supersaturated solid solution; during the aging treatment, the aging temperature is 150-200°C, the heating rate is 5°C / min, and the holding time is 6-10h.

Citation Information

Cited By

  • Method for preparing B4C / Ti6Al4V composite material through laser melting deposition and application of B4C / Ti6Al4V composite material

    CN121104115A